Characteristic distribution of peripapillary retinal nerve fibre layer oedema in acute methanol-induced optic neuropathy - Maritz, Francois (Division of General Surgery, 2025)
Aims: To describe a characteristic distribution of peripapillary retinal nerve fibre layer oedema in acute methanol-induced optic neuropathy (Me-ION). Methods: This retrospective case series study included four adult patients with acute Me-ION treated at Groote Schuur hospital in Cape Town during the national alcohol ban amid the COVID-19 pandemic from 27 March 2020 to 31 May 2020. Clinical examination included a best corrected visual acuity, pupillary light reflex assessment, anterior segment slit-lamp examination, and dilated fundoscopy. Fundus photography and retinal nerve fibre layer (RNFL) thickness by optical coherence tomography (OCT) was performed. Results: All patients were examined during the acute phase of Me-ION, with a mean interval of 5.5 days between methanol exposure and ocular examination. Fundoscopy showed peripapillary retinal nerve fibre layer whitening and oedema, which extended superiorly and inferiorly from the optic disc and followed the vascular arcades but spared the nasal and temporal areas. In three cases, this correlated with a distinctive pattern of superior and inferior quadrant RNFL thickening on OCT with relative sparing of the nasal and temporal quadrants. Conclusion: Our study is the first to associate this fundoscopic finding with the distinctive superior and inferior quadrant RNFL oedema on OCT during the acute phase of Me-ION. Recognition of this pattern can aid in early diagnosis and timely initiation of life-saving treatment, particularly in cases where patients may be unaware of their methanol exposure.